Driving Social Commerce Adoption in Indonesia: The Role of Trust, Reviews, and Platform Features - Asri Sundari; R Dewi Pertiwi (Sean Institute, 2025)
Developments in information and communication technology have supported the emergence of social commerce as a new form of online transactions that combines the functions of social media and e-commerce. This study aims to deeply understand the factors driving social commerce adoption in Indonesia, focusing on trust, reviews, and platform features. The study was conducted using a qualitative approach with descriptive methods. The results indicate that trust, user reviews, and platform features play a significant role in driving social commerce adoption in Indonesia. Trust has been shown to be a key factor influencing purchasing decisions, with information transparency, transaction security, and seller reputation contributing significantly to consumers' sense of security. User reviews serve as social proof, helping potential buyers assess product quality and seller reliability, while interactive features such as live shopping and user-generated content enhance engagement and the shopping experience. Overall, the combination of trust, social support through reviews, and innovative platform features creates a more credible and engaging social commerce ecosystem for Indonesian consumers.